Tax Corruption and Parallel Economy (The Social Irresponsibility of Tax Avoidance Practice) - Madhulika (Journal of Commerce and Trade, 2008)
Indian economy is undergoing a sea change. Most of the economic models have tilted towards markets. This phase of globalisation has not only prompted change in the way of doing business but also touched significantly upon the everyday life of common man, his needs, and aspirations. The Social Irresponsibility of Tax Avoidance Practice is perhaps the most fundamental way in which private and corporate citizens engage with broader society. It is therefore curious that tax minimization through elaborate and frequently aggressive tax avoidance strategies are is regarded as one of the prime duties that directors are required to perform on behalf of their shareholders. It is even more curious that the debate about corporate responsibility which has touched on virtually every other area of corporate engagement with broader society has scarcely begun to question companies in the area where their corporate citizenship is most tangible and most important – the payment of tax. The free market tax competition model assumes that all tax-paying citizens and businesses are perfectly mobile and therefore able to migrate between different jurisdictions according to preference. Ironically the majority of tax havens have adopted elaborate defence strategies to prevent such migratory flows, but the otherworldliness of the perfect mobility assumption has not deterred these arguments in defence of the ‘discipline’ imposed by tax heavens.